Differential evolutionary algorithm for distribution capacitor allocation considering varying load conditions - Karimi, Mohammad (Видавництво Львівської політехніки, 2011)
Many loads in power systems are inductive loads then consume reactive power, this fact lead to drop voltage and in worst case blackout and collapse voltage. Best option in distribution networks for avoid of this problem is installation of capacitor bank. In capacitor installation, finding optimal location and size of capacitor have special importance. In this paper, Differential Evolutionary (DE) algorithm is proposed for optimal placement and sizing of capacitor. Our objective function includes the minimization of investment costs and energy losses. Load of network has been considered in three levels. The proposal method has been tested on 34-bus radial distribution system and results of simulation have been compared with several valid reference.
Диференціальний еволюційний алгоритм для розгляду розміщення розподільного компенсатора при змінних режимах навантаження
Keywords: Differential Evolutionary (DE) Algorithm; Optimal Capacitor Placement; Radial Distribution Network; Varying Loads